Tribal economy at crossroads - Chaudhary, S. N. (Rawat Publications, 2010)
Revised version of papers presented at a national seminar held at Bhopal during 11-12 February 2009 organized by Rajiv Gandhi Chair in Contemporary Studies, Barkatullah University.